Gestão da informação em pequenas e médias empresas: o impacto das tecnologias de inforamção na Auto Comercial Diamantina S.A - Maria da Graca Eulalio de Souza Bertucci (2003)
This research focused on the description and analysis of the impact of information and communication technologies - IT - in the information management of small and medium size enterprises - SME. So, a medium-sized, non-metropolitan company located in Diamantina, Minas Gerais was selected. Auto Comercial Diamantina S.A. is an authorized Volkswagen car dealer. As the study intended to analyze the relation of IT in information management, considering cultural influences of the organization and the characteristics of SME, the following analysis categories were established and studied: (a) types of information and communication technologies that were utilized; (b) influence of Volkswagen in information use; (c) motivational factors for the use of information technologies; (d) aspects of the cultural background of the company; (e) perceived barriers during the use of those technologies; (f) impacts of information and communication technologies noticed during collection, distribution and information use in the selected information systems. The analytic structure of the impact of the technologies of information and communication on the company was based on the structural model of Orlikowski. This model was the source for all discussions that were performed. It was noticed that the interaction between users, company and IT is influenced by the characteristics of the technological artifact, by the characteristics of social agents, by the cultural context and by the way that people interpret and use these technologies. The three main consequences of the insertion of IT in Auto Comercial were more information access, incremental innovations and greater reliability of internal information. It was also verified that the use of IT in Auto Comercial didn't bring any direct influence on its profitability. Its presence, though, helps the company to stay afloat and to search for alternatives in this presently unfavorable environment. The conclusions regarding the contribution of IT to information management of small and medium size companies indicate that the technological infrastructure and the diffusion of IT, guarantee neither the insertion of SME in the economy of innovation nor the increases in competitiveness due to modernization of their telecommunication infrastructures. Gains of competitiveness may happen when the adoption of IT is inserted in a larger process, in a strategy that involves knowledge of organizational values, structural reforms, training and policies of local and state incentives. Explicitly regarding information, the adoption of IT is not a guarantee for solving all matters related to its processing and dissemination in SME. When there is integration between man and technology, through social and cultural relations, the company may ensure the best benefit of the know-how of its employees, the sharing of ideas and information. That is where resides the importance of the information management in the context of small and medium size companies.